Synthesis of Green Method for Improving Soil Quality Using Domestic Solid Waste - M. V. Raju, Cyril Lucy Monica, D. Satyanarayana, M. Satish Kumar, K. Maria Das (International Journal of Advanced Science and Technology, 2020)
Solid waste monitoring and management is going to occupy an immediate and urgent strategic handling issue to all over the world as its level of influence is gradually increasing year by year by crossing it’s ownterritorieswith a set of challenging issues in concern with environmental consequences and the other issues related to the developmental activities of that particular area.As far as current scenario of solid waste there is an urgency to address all such type of issueswith an immediate concern throughout globe. In the current context of natural resources, majority of them are depleting at an alarm rate in order to meet daily needsfor the wast growing population of the world more particularly prime natural resources such as air water and soil.The occupancy of solid waste at almost all the parts of the world had been increasing by creating land scarcity problem forpromoting different developmental activities to increase the quality living standards of the nearby people. In this present study we have focused on domestic solid waste and proposed a concept of converting domestic solid waste into a useful accelerator like fuel for the Improvement of soilcharacteristics that drivessociety into various innovative and logical models for the effective utilization of domestic solid waste.